2017
DOI: 10.1164/rccm.201606-1107ci
|View full text |Cite
|
Sign up to set email alerts
|

Early Lung Disease in Infants and Preschool Children with Cystic Fibrosis. What Have We Learned and What Should We Do about It?

Abstract: The past decade has seen significant advances in understanding of the pathogenesis and progression of lung disease in cystic fibrosis (CF). Pulmonary inflammation, infection, and structural lung damage manifest very early in life and are prevalent among preschool children and infants, often in the absence of symptoms or signs. Early childhood represents a pivotal period amenable to intervention strategies that could delay or prevent the onset of lung damage and alter the longer-term clinical trajectory for ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
85
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 87 publications
(113 reference statements)
1
85
0
4
Order By: Relevance
“…The number of exacerbations with advancing age may have a cumulative detrimental effect on pulmonary function . The relationship between an acute exacerbation in CF and PSG abnormalities such as significant hypoxemia has not been studied in detail before.…”
Section: Discussionmentioning
confidence: 99%
“…The number of exacerbations with advancing age may have a cumulative detrimental effect on pulmonary function . The relationship between an acute exacerbation in CF and PSG abnormalities such as significant hypoxemia has not been studied in detail before.…”
Section: Discussionmentioning
confidence: 99%
“…Morbidity and mortality in CF relate primarily to progressive lung damage, leading eventually to respiratory failure. Although some studies point to anomalies in prenatal development of large airways in CF (2), the first overt symptoms may be detected months to years after birth (3)(4)(5), primarily because of involvement of the small airways (6). Thanks to newborn screening, CF infants can be diagnosed within a few weeks of birth and monitored closely from a very young age, which has led to improved patient care and outcomes (7).…”
mentioning
confidence: 99%
“…Nearly 20 years have revealed that children with CF develop signs of lung disease early in life (5,11,12). Inflammation as evidenced by increased levels of proinflammatory mediators and downstream recruitment of blood neutrophils into the airway lumen occurs within a few weeks after birth (13).…”
mentioning
confidence: 99%
“…The low incidence of abnormal findings on CXR and lack of association between CXR score and growth suggests the need for a more sensitive indicator of lung disease in these infants. High-resolution chest computed tomography (CT) and bronchoalveolar lavage (BAL) are more effective at detecting early lung disease but are more invasive 3 . The multiple breath washout technique has been used to calculate Lung Clearance Index (LCI), a measure of ventilation inhomogeneity.…”
Section: Discussionmentioning
confidence: 99%